Achievement motivation for band: A cross-cultural examination of the 2 × 2 achievement goal motivation framework. (November 2016) - Miksza, Peter; Tan, Leonard; Dye, Christopher
The purpose of this study was to explore the achievement goal motivation orientations of instrumental music students in the US and Singapore. Participants in this study were volunteer band students ( N = 359) from eight American public high schools ( n = 217) and five polytechnics in Singapore ( n = 142). Data were collected via a questionnaire that included measures of (a) the 2 × 2 achievement goal orientation constructs (mastery approach, mastery avoid, performance approach, and performance avoid), (b) flow in band rehearsal, (c) grit in practicing, and (d) commitment to band. Confirmatory factor analyses indicated that the 2 × 2 achievement goal framework specifying four latent variables (mastery approach, mastery avoid, performance approach, performance avoid) was the best relative fit to the data when compared with competing dichotomous and trichotomous models. In contrast to previous research comparing achievement goals of learners from collectivistic and individualistic cultures, no significant differences in achievement goal sub-scale means were found as a function of culture. However, some differentiated patterns of relationship were found between the achievement goal sub-scales and flow, grit, and commitment to band as a function of culture.